The Behavior of the Student in the Ancient Iraqi School During the Third Millennium BCE - Ibrahim, Asst. Lecturer Amna Salem Ibrahim (Sulaimani Journal for Humanities, 2026)
Education is the foundational building block that a child receives from an early age. It serves as a powerful tool in shaping personality and developing intellect, ultimately guiding the individual toward success, growth, and advancement. The primary goal of education—whether in ancient or modern times—has always been to instill proper behavior, discipline, commitment, and character development, all of which yield positive outcomes for both the individual and society. Throughout their schooling years, students acquire a wealth of knowledge that helps them comprehend the nature of the universe and human character within an educational framework. A graduate who holds an official certificate often gains respect and appreciation in society. In ancient Iraq, life was organized according to spiritual guidance received by priests from the gods, directing individuals to adopt ethical and educational principles that fostered social respect and sustainable intellectual development. The core purpose of education in ancient, formal schools was to provide students with a moral and intellectual foundation shaped by divine instruction. This premise inspired the researcher to explore this subject with precision, focusing on a key trait of the ancient Iraqi student: their respectful behavior toward teachers and obedience to their parents, especially when preparing to attend school. This behavior played a vital role in promoting noble values and ethical conduct. Thus, education in ancient Iraq was seen as a product of cultural refinement and a true reflection of society.
Keywords: Behavior; Education; Student; School